(untitled) - Hair, Joseph F. (Boston, 2006)
Marketing Research, 3/e takes an application-oriented approach, providing students with the tools and skills necessary to solve business problems and exploit business opportunities. This book is unique from any other in the market in three significant ways. First, it provides a greater balance between primary and secondary information and the techniques and methods that underpin these two important types of data. Second, it offers in-depth coverage of the critical research tools and skills that will be required of today and tomorrow’s marketing researchers and business decision-makers. Third, with its in-depth coverage of secondary research, the practice of customer-based management is highlighted as this book helps students see what real companies are doing for their marketing research. This book provides students a realistic and current view of the practice and importance of marketing research in the business world.
Keywords: Marketing research